Studies in Early Middle English Loanwords: Norse and French Influences – Lectio praecursoria - Skaffari Janne (MODERN LANGUAGE SOC, 2022)
The author defended his doctoral dissertation Studies in Early Middle English Loanwords: Norse and French Influences (Anglicana Turkuensia 26. Turku 2009) at the Faculty of Humanities, University of Turku, on 2nd October, 2009. The official opponent at the public defence was Professor Juliette Dor (University of Liege), and the defence was chaired by Professor Risto Hiltunen (University of Turku). The following is an English-language summary of the introductory talk delivered in Finnish at the start of the viva.